Matrix support in mental health: achievements and limits in primary health care - Morais, Ana Patrícia Pereira; Tanaka, Oswaldo Yoshimi (Saúde e Sociedade, 2012)
Changes in mental health care in the city of Fortaleza (Northeastern Brazil) have a recent historical and political process. Compared to other municipalities of the State of Ceará, which in the early 1990s were already pioneers in the process, Fortaleza has not implemented the changes due to the interests of psychiatric hospitals, of psychiatric outpatient clinics of the public network, and because of the difficulty in managing the new mental health devices and equipment present in Primary Care. In the municipality, the reorganization of mental health actions and services has required that the Primary Care Network faces the challenge of assisting mental health problems with the implementation of Matrix Support. In light of this context, we aimed to evaluate Matrix Support in mental health in Primary Care Units and to identify achievements and limitations in the Primary Care Units with Matrix Support. This study used a qualitative approach and was carried out by means of a case study. We interviewed twelve professionals from the Family Health Teams of four Units with implemented Matrix Support. The analysis of the information reveals that access, decision making, participation and the challenges of implementing Matrix Support are elements that are, in a dialectic way, weak and strong in the reorganization of services and practices. The presence of Matrix Support in Primary Care highlights the proposal of dealing with mental health within the network in the municipality. The process has not ended. Mobilization, awareness-raising and qualification of Primary Care have to be enhanced constantly, but implementation has enabled, to the service and professionals, greater acceptance of mental health in Primary Care.